Factors influencing marketing of vegetables among small holder farmers: A study of tomato value chain in Ruvu Kibaha District - Fredrick, Oliver (Mzumbe University, 2026)
A dissertation submitted in fulfillment of the requirement for the award of the degree of Master of Business Administration (MBA) in Corporate Management of Mzumbe University